IMPROVING EXISTING DESIGN GUIDANCE OF OFFSHORE BREAKWATER FOR PREDICTING SHORELINE RESPONSE TO SUBMERGED BREAKWATER - QAYOOM TUNJI, LAWAL ABDUL (2015)
Emergent coastal structures, such as groynes, detached offshore breakwaters and sea walls have been successfully adopted as coastal protection measures for many decades_ However, environmentally aware modem communities are beginning to prefer engineering structures that are less intrusive and more aesthetically appealing_ As a result, submerged breakwaters (SBWs), which do not impair beach amenity or aesthetics, are becoming a preferred option for coastal protection_ But, SBWs have rarely been adopted for coastal protection in the past and therefore, their efficacy remains largely unknown_ Also, enhanced shoreline erosion has been reported in the lee of the structure of several SBW projects_ The non-performance of these SBW facilities have been attributed to the lack of performance data of SBW and the use of existing design guidance of offshore breakwater to predict shoreline response at the lee of such structure_ Henceforth, this study endeavored to improve these existing design guidance for predicting shoreline response at the lee of SBW.